Essays on the political economy of development: Determinants of political and economic behavior - Gustav Agneman (University of Copenhagen, Department of Economics, 2020)
This PhD dissertation consists of four self-contained chapters in the field of Political Development Economics. They are all empirical projects studying decision-making under heterogeneous conditions. In the first chapter, I investigate the causal link between economic expectations and voting in an independence referendum, and document that the effect is contingent upon voters' identity. In the second chapter we map state capacity at the subnational level in Africa and show that the risk of oil induced conflicts depends on levels of local state capacity. The third chapter focuses on the link between food scarcity and cooperative investments. Exploiting the harvest as an exogenous shock to food supply in rural Tanzania, we document a causal role of food scarcity in suppressing socially efficient cooperation. The fourth and final chapter studies moral decision making in Greenland. We develop a measure of parochial honesty - the propensity to behave honestly toward the ingroup but not toward the outgroup - and show that market exposure predicts the degree of group differentiation.
Keywords: 330